KEBUTUHAN PENGELOLAAN WISATA DI PULAU GILI LABAK, SUMENEP: EUFORIA DESTINASI WISATA BARU - Fery Kurniawan; Robba Fahrisy Darus; Irfanudin Rizaki (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
Gili Labak Island has a very beautiful natural potential, both on land and sea. Location close to the mainland make this small island a new tourism destination that is in demand of local and regional travelers and able to create new economic resources. The euphoria is creating new pressures on the environment and coastal ecosystems, especially the lack of detailed tourism management on the island, so that tourists and tourism actors that come in large numbers to perform activities freely without regard to the existing the vulnerability and the carrying capacity of ecosystems. The paper focuses on the impacts and the responses of existing and needed to build sustainable tourism of small island travel. A DPSIR (drivers, pressures, states, impacts and responses) framework is used to explore the causes and consequences on coastal ecosystems of tourism activities that is not managed properly, so the management can be arranged as needed. Detailed zoning system and the ecotourism concept needs to be applied according to the vulnerability, carrying capacity and resilience of the ecosystem of the island. Increasing the capacity of the community and travel must be conducted to ensure the sustainability of tourism and the island management.